2023
DOI: 10.1024/0300-9831/a000723
|View full text |Cite
|
Sign up to set email alerts
|

The negative relationship of dietary inflammatory index and sleeping quality in obese and overweight women

Abstract: Abstract. Background and aims: Substantial evidence have linked low grade inflammation with the pathophysiology of chronic diseases and psychological impairment. An integral component underlying the link is pro-inflammatory diet. While sleeping is another significant contributor, few studies have addressed the relationship between the sleep quality and inflammatory cascade with the dietary quality as a moderator. The current study assesses the relation between inflammatory potential of the diet and sleep quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The remainder of the studies were conducted in young-to-middle-aged unhealthy adults [ 18 , 22 , 25 , 27 ]. While studies conducted in overweight and/or obese individuals found significant associations between higher scores on the DII and poor sleep quality [ 18 , 22 ] (apart from Tabrizi and Farhangi, 2021 [ 28 ]), other studies showed no significant association between the DII and sleep quality in individuals with sleep apnea [ 27 ] and fibromyalgia [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remainder of the studies were conducted in young-to-middle-aged unhealthy adults [ 18 , 22 , 25 , 27 ]. While studies conducted in overweight and/or obese individuals found significant associations between higher scores on the DII and poor sleep quality [ 18 , 22 ] (apart from Tabrizi and Farhangi, 2021 [ 28 ]), other studies showed no significant association between the DII and sleep quality in individuals with sleep apnea [ 27 ] and fibromyalgia [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies conducted in obese and/or overweight individuals showed an association between reduced sleep quality and adherence to pro-inflammatory dietary patterns [ 18 , 22 ] (apart from Tabrizi and Farhangi, 2021 [ 28 ]; in which the null finding could be driven by the different statistical analysis technique, namely, the structural equational modeling, used). However, a similar pattern of results was not observed in studies conducted in populations with pain-related disorders or sleep-related breathing disorders [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the DII was treated as a continuous variable and not categorized into quartiles, significance was observed only for the adjusted model. 32 Another study 33 with the same objective and conducted only with women found that the participants with higher DII scores had worse sleep quality evaluated by the PSQI. 33 Godos et al 34 (2019) conducted the same study with adults and older adults from Southern Italy and observed that participants in the highest quartile of the DII were less likely to have adequate sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…32 Another study 33 with the same objective and conducted only with women found that the participants with higher DII scores had worse sleep quality evaluated by the PSQI. 33 Godos et al 34 (2019) conducted the same study with adults and older adults from Southern Italy and observed that participants in the highest quartile of the DII were less likely to have adequate sleep quality. 34 Similarly, Wirth et al 35 (2020) investigated whether an improvement in the E-DII score after 3 months of intervention with nutritional guidance, physical exercise, and stress reduction would be associated with an improvement in sleep parameters measured by actigraphy.…”
Section: Discussionmentioning
confidence: 99%